MicroRNA therapy stimulates uncontrolled cardiac repair after myocardial infarction in pigs - Gabisonia, Khatia; Prosdocimo, Giulia; Aquaro, Giovanni Donato; Carlucci, Lucia; Zentilin, Lorena; Secco, Ilaria; Ali, Hashim; Braga, Luca; Gorgodze, Nikoloz; Bernini, Fabio; Burchielli, Silvia; Collesi, Chiara; et al. (Nature (London), 2019)
Prompt coronary catheterization and revascularization have markedly improved the outcomes of myocardial infarction, but have also resulted in a growing number of surviving patients with permanent structural damage of the heart, which frequently leads to heart failure. There is an unmet clinical need for treatments for this condition 1 , particularly given the inability of cardiomyocytes to replicate and thereby regenerate the lost contractile tissue 2 . Here we show that expression of human microRNA-199a in infarcted pig hearts can stimulate cardiac repair. One month after myocardial infarction and delivery of this microRNA through an adeno-associated viral vector, treated animals showed marked improvements in both global and regional contractility, increased muscle mass and reduced scar size. These functional and morphological findings correlated with cardiomyocyte de-differentiation and proliferation. However, subsequent persistent and uncontrolled expression of the microRNA resulted in sudden arrhythmic death of most of the treated pigs. Such events were concurrent with myocardial infiltration of proliferating cells displaying a poorly differentiated myoblastic phenotype. These results show that achieving cardiac repair through the stimulation of endogenous cardiomyocyte proliferation is attainable in large mammals, however dosage of this therapy needs to be tightly controlled. MicroRNAs delivered by adeno-associated viral vectors improve global and regional contractility, increase muscle mass and reduce scar size in a porcine model of myocardial infarction.